Design and Development of a Web-Based E-Commerce System for Eco-Friendly Product Sales at PT. Cakra Tekno Nusantara - Sabilillah, Fiki Kautsar; Sharyanto, Sharyanto; Bani, Alexius Ulan (Yayasan Bina Internusa Mabarindo, 2025)
The development of information technology has changed how businesses operate, especially in the commerce sector. PT. Cakra Tekno Nusantara, through its Any Sustainability platform, still faces limitations in transaction management and inventory tracking. This research aims to design and develop a web-based e-commerce system to enhance transaction efficiency and support the sale of eco-friendly products. The methods include observation, interviews, literature studies, and system development using Unified Modeling Language (UML), followed by Black Box Testing. The results show that the system can automate transaction processes, product management, and order tracking. This implementation improves operational efficiency and supports the company’s sustainability mission.